Pengaruh Pemberian Edukasi Gizi dengan Media Permainan Ular Tangga terhadap Pengetahuan, Sikap, Asupan Protein dan FE pada Remaja Putri - Salsabila Demitha Mahdira; Hidayatusy Syukrina Puteri; Adhi Nurhartanto (Jurnal Kebidanan dan Keperawatan Medika, 2026)
Anemia is a common health problem among female adolescents due to inadequate nutrient intake, particularly protein and iron (Fe). Effective nutrition education is essential to improve knowledge, attitudes, and behaviors related to optimal nutritional intake. One method that can be applied is the Snakes and Ladders game. This study aims to examine the impact of nutrition education through the Snakes and Ladders game on knowledge, attitudes, and protein and iron intake among eleventh-grade female adolescents at SMAN 1 Menggala. A quasi-experimental pretest-posttest control group design was employed. The sample consisted of 67 eleventh-grade female students divided into control and intervention groups. The control group received educational material using PowerPoint, while the intervention group received PowerPoint presentations combined with the Snakes and Ladders game. Data were analyzed using the Mann-Whitney test. A significant increase in knowledge was observed (), whereas no significant impact was found on attitudes (). Significant increases were recorded for both protein consumption () and iron consumption (). Overall, the intervention group demonstrated greater score improvements compared to the control group. The use of the Snakes and Ladders game for nutrition education effectively enhances knowledge as well as protein and iron intake among female adolescents. This media serves as an engaging and easy-to-understand educational alternative to help reduce anemia in adolescents.